The influence of islamic culture on maimonides in the development of Mishnah's legislation - Ali, Walid Reda; Abo-Elmagd, Lila (Penerbit Universiti Kebangsaan Malaysia, 2023)
Maimonides, as a jurist, aimed to develop the Mishnah's legislations; so, he wrote his book Mishnah Torah, which included the Mishnah's legislations, and added to it legislations to fill the gap in provisions of the Mishnah. Maimonides used the books of the rabbinic heritage to complete this deficiency in the legislation. He reclassified these legislations objectively in his book Mishnah Torah, which he wrote in Egypt in 1117 AD, according to the method of Islamic jurisprudence books and Al-Muhalla by Ibn Hazm in particular. The current paper discusses the classification and division of the Mishnah and the Mishnah Torah, in order to find out the legislations that Maimonides added to the Mishnah. Also, it clarifies Maimonides' motive for authoring Mishnah Torah. Additionally, this paper illustrates how the Islamic culture influenced on the classification and division of the Mishnah Torah according to the subject. Clearly, Maimonides was influenced in his book Mishnah Torah by Islamic jurisprudence and the book of Ibn Hazm; Al-Muhalla in particular. He reclassified some legislationsin Mishnah Torah objectively according to a method of Islamic jurisprudence books.